2004
DOI: 10.1074/jbc.m407782200
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Mycobacterial Rhamnosyltransferase, Which Is Needed for the Formation of the Arabinogalactan-Peptidoglycan Linker, Leads to Irreversible Loss of Viability

Abstract: The acid-fastness of all mycobacteria is based upon a shared universal cell wall core structure. The mycobacterial cell wall consists of an outer lipid layer and an inner peptidoglycan layer. The outer layer is highly impermeable and is composed of unique 70 -90 carbon-containing lipids, known as mycolic acids. The mycolic acids are esterified to the non-reducing terminal arabinosyl residues of the polysaccharide arabinogalactan (1-5). The reducing end of arabinogalactan is connected to the peptidoglycan via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
75
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 27 publications
1
75
0
Order By: Relevance
“…6B). Indeed, Rv2962c, Rv2957, and Rv2958c are involved in the glycosylation of phenolglycolipids of M. tuberculosis (41) and Rv3265c is required for the attachment of the rhamnosyl unit of the arabinogalactan to the peptidoglycan (35). Although the predicted glycosyltransferases of M. tuberculosis (Rv1524 and Rv1526c) and M. leprae (ML2348) are located on branches distinct from those of M. smegmatis and M. avium (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6B). Indeed, Rv2962c, Rv2957, and Rv2958c are involved in the glycosylation of phenolglycolipids of M. tuberculosis (41) and Rv3265c is required for the attachment of the rhamnosyl unit of the arabinogalactan to the peptidoglycan (35). Although the predicted glycosyltransferases of M. tuberculosis (Rv1524 and Rv1526c) and M. leprae (ML2348) are located on branches distinct from those of M. smegmatis and M. avium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4B). As described recently, the polar GPLs differ from the apolar GPLs by the addition of a rhamnosyl residue (triglycosylated GPLs) or a succinyl residue (succinylated GPLs) linked to the terminal rhamnosyl unit (35,47) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mAGP represents one of the most important cell wall components of members of the Corynebacterianeae, and it is essential for the viability of M. tuberculosis (27)(28)(29). It acts as a fulcrum between peptidoglycan and the impermeable hydrophobic mycolic acid layer.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that both EmbA and EmbB are involved in the formation of the terminal Ara 6 motif in AG, and EmbC in the formation of arabinan in lipoarabinomannan (26). Our preliminary attempts to obtain deletion mutants of embA and embB in M. tuberculosis or embAB in M. smegmatis have proved unsuccessful, 7 presumably due to the essentiality of cell wall mAGP (27)(28)(29).…”
mentioning
confidence: 99%